IMPLEMENTASI KURIKULUM PENDIDIKAN DI MA’HAD AL ISLAM GUMUK SURAKARTA: INTEGRASI PENDIDIKAN ISLAM, PEMBENTUKAN KARAKTER, DAN DINAMIKA PERSEPSI PUBLIK - Ibnu Khotim; Yusuf Arifin; Muhammad Isa Anshory (JIPDAS (Jurnal Ilmiah Pendidikan Dasar), 2026)
Islamic boarding educational institutions play a strategic role in character development, strengthening Islamic identity, and improving students’ competencies. In the midst of increasingly complex social dynamics, curriculum implementation in Islamic educational institutions is required not only to integrate scientific and spiritual dimensions but also to respond to various public perceptions emerging in society. This article aims to analyze the implementation of educational curriculum at Ma’had Al Islam Gumuk Surakarta through a literature study approach by reviewing scholarly sources related to Islamic boarding education, Islamic curriculum, character formation, and public perceptions of Islamic educational institutions. The study reveals that curriculum implementation in Islamic boarding schools is generally constructed through the integration of religious education, moral development, Arabic language learning, mastery of Islamic sciences, and the cultivation of academic and spiritual culture. Furthermore, Islamic educational institutions often encounter challenges related to public perceptions influenced by social, political, and media factors. Therefore, curriculum implementation should be understood not merely as an academic process but also as an effort to foster moderation, character development, and public trust in Islamic educational institutions. This study contributes to the development of a more adaptive, integrative, and socially relevant Islamic educational curriculum.